High-efficiency hydrogen evolution reaction photocatalyst for water splitting of Type-II β-AsP/g-C3N4 van der Waals heterostructure. (29th March 2023) - Zhao, Huiyan; Jia, Baonan; Wang, Zihao; Han, Lihong; Song, Haizhi; Lu, Pengfei
Abstract: Photocatalytic for water splitting to produce hydrogen is recognized as a low-cost, promising and attractive method to solve environmental problems and energy crises, but finding a high-performance photocatalyst is a big challenge. In this work, we designed a type-II β-AsP/g-C3 N4 van der Waals heterostructure as an efficient photocatalyst and had the first principles calculations to analyze its stability, electronic properties, and photocatalytic performance. The results showed that the photocatalyst of β-AsP/g-C3 N4 heterostructure met the proper band gap and band edge of the redox potential of water splitting, had effective charge separation of photogenerated electronic holes, and efficient visible light response. Importantly, our research showed that the β-AsP/g-C3 N4 heterostructure could proceed spontaneously in thermodynamics and had an excellent photocatalytic performance in further study. It had quite good hydrogen evolution performance with the Gibbs free energy of −0.02 eV, which is closer to zero than −0.09 eV of Pt (111). The overpotential of its oxygen evolution reaction is as low as 0.57 V. This work showed excellent development prospects for β-AsP/g-C3 N4 heterostructure in the field of photocatalysts, which will promote the development of g–C3 N4 –based photocatalytic for water splitting. Highlights: β-AsP/g-C3 N4 heterostructure is a promising high-efficiency photocatalyst for water splitting. β-AsP/g-C3 N4 heterostructure was found to have the ΔGH more closed to zero than Pt (111). The overpotential of β-AsP/g-C3 N4 heterostructure in OER is as low as 0.57 V.